Tabernaemontana catharinensis leaves exhibit topical anti-inflammatory activity without causing toxicity. (1st March 2019) - Camponogara, Camila; Casoti, Rosana; Brusco, Indiara; Piana, Mariana; Boligon, Aline A.; Cabrini, Daniela Almeida; Trevisan, Gabriela; Ferreira, Juliano; Silva, Cássia Regina; Oliveira, Sara Marchesan
Abstract: Background: Tabernaemontana catharinensis, popularly known as snake skin, has been empirically used as an anti-inflammatory to treat cutaneous skin disorders. However, no study proves its effectiveness as a topical anti-inflammatory. Study design: We investigated the topical anti-inflammatory effect of T.catharinensis leaves crude extract (TcE) in irritant contact dermatitis models in mice and its preliminary toxicity profile. Methods: The topical anti-inflammatory effect was evaluated by ear thickness measurement, inflammatory cell infiltration (MPO activity measurement and histological procedure) and cytokines levels. TcE qualitative phytochemical analysis was performed by UHPLC-ESI-HRMS and the TcE effect (therapeutic dose; 10 µg/ear) on preliminary toxicological parameters was also evaluated (on the 14° day of experiment). Results: TcE (10 μg/ear) prevented the development of ear edema induced by cinnamaldehyde, capsaicin, arachidonic acid, phenol, and croton oil with maximum inhibition of 100% to cinnamaldehyde, arachidonic acid, phenol, and croton oil and 75 ± 6% to capsaicin. Besides, the TcE (10 μg/ear) also prevented the increase of MPO activity by 96 ± 2%, 48 ± 7%, 100%, 87 ± 8%, and 93 ± 4%, respectively, to the same irritant agents. The positive controls also prevented both ear edema and the increased of MPO activity by 100% and 42 ± 8% (HC-030031), 54 ± 6% and 80 ± 4% (SB-366791), 100% and 54 ± 5% (indomethacin), 100% and 80 ± 4% (dexamethasone in skin inflammation model induced by phenol) and 100% and 97 ± 3% (dexamethasone in inflammation model induced by croton oil), respectively. TcE also prevented the inflammatory cells infiltration and the increase of MIP-2, IL-1β and TNF-α levels irritant agents-induced. TcE topical anti-inflammatory effect may be attributed to the combined effect of indole alkaloids, terpenes, and phenolic compounds found in the extract and identified by dereplication method. The TcE' therapeutic dose proved to be safe in preliminary toxicological tests. Conclusion: Our results suggest that TcE could be an interesting strategy for the treatment of inflammatory diseases. Graphical abstract: